Neutrophil Immunomodulatory Activity of (−)-Borneol, a Major Component of Essential Oils Extracted from Grindelia squarrosa - Igor A. Schepetkin; Gulmira Özek; Temel Özek; Liliya N. Kirpotina; Andrei I. Khlebnikov; Mark T. Quinn (Molecules, 2022)
Grindelia squarrosa (Pursh) Dunal is used in traditional medicine for treating various diseases; however, little is known about the immunomodulatory activity of essential oils from this plant. Thus, we isolated essential oils from the flowers (GEOFl) and leaves (GEOLv) of G. squarrosa and evaluated the chemical composition and innate immunomodulatory activity of these essential oils. Compositional analysis of these essential oils revealed that the main components were α-pinene (24.7 and 23.2% in GEOFl and GEOLv, respectively), limonene (10.0 and 14.7%), borneol (23.4 and 16.6%), p-cymen-8-ol (6.1 and 5.8%), β-pinene (4.0 and 3.8%), bornyl acetate (3.0 and 5.1%), trans-pinocarveol (4.2 and 3.7%), spathulenol (3.0 and 2.0%), myrtenol (2.5 and 1.7%), and terpinolene (1.7 and 2.0%). Enantiomer analysis showed that α-pinene, β-pinene, and borneol were present primarily as (−)-enantiomers (100% enantiomeric excess (ee) for (−)-α-pinene and (−)-borneol in both GEOFl and GEOLv; 82 and 78% ee for (−)-β-pinene in GEOFl and GEOLv), while limonene was present primarily as the (+)-enantiomer (94 and 96 ee in GEOFl and GEOLv). Grindelia essential oils activated human neutrophils, resulting in increased [Ca2+]i (EC50 = 22.3 µg/mL for GEOFl and 19.4 µg/mL for GEOLv). In addition, one of the major enantiomeric components, (−)-borneol, activated human neutrophil [Ca2+]i (EC50 = 28.7 ± 2.6), whereas (+)-borneol was inactive. Since these treatments activated neutrophils, we also evaluated if they were able to down-regulate neutrophil responses to subsequent agonist activation and found that treatment with Grindelia essential oils inhibited activation of these cells by the N-formyl peptide receptor 1 (FPR1) agonist fMLF and the FPR2 agonist WKYMVM. Likewise, (−)-borneol inhibited FPR-agonist-induced Ca2+ influx in neutrophils. Grindelia leaf and flower essential oils, as well as (−)-borneol, also inhibited fMLF-induced chemotaxis of human neutrophils (IC50 = 4.1 ± 0.8 µg/mL, 5.0 ± 1.6 µg/mL, and 5.8 ± 1.4 µM, respectively). Thus, we identified (−)-borneol as a novel modulator of human neutrophil function.